Aplicación de la técnica historieta para desarrollar la producción de textos escritos en alumnos/as del 3er grado de primaria, de la I.E N°00622 El Porvenir - Collantes Nauca, Juana Rosa (2014)
The purpose of this research was to apply the technique cartoon to develop the production of texts in children in the thírd grade of prímary educatíonal of School No. 00622 El Porvenir Ríoja -2014. To meet the objectives, was based on studíes of the hístory of research, theories of enunciation, lmaginary both cartoons and production of texts in which the study variables were conceptualized. Such theoretical framework allowed the following hypothesis: "The Technical Cartoon significantly improve the production of written texts in the third grade student's of elementary educational of School No. 00622 El Porvenir- Rioja". The quasi-experímental research design with pretest and posttest two groups. The sample consisted of 40 student's in the third grade of prímary education, undergo a test and development of the art cartoon eíght learning sessíons. At the conclusion ,of the investigatíon, ít was found that the application of the technique cartoon has ·achieved a production of texts developed in the student's of the third degree in -the experimental group of School No. 00622 "El Porvenir" district of Rioja- 2013 T calculated value (47.82) than the tabulated t value (1.684).